The effect of educational exercises with the Edga model on the performance of the skills of preparation and overwhelming volleyball beating for students - adel, shiamaa; Alloun, Nihad (Journal of Physical Education, 2025)
The aimed of the research to prepare educational units with the Edge model in performing the skills of the overwhelming preparation and beating of volleyball for students of the second stage in the College of Physical Education and Sports Science, and to know the impact of educational units with the Edga model in performing the skills of preparation and overwhelming volleyball among students of the second stage in the College of Physical Education and Sciences Sports, and the researchers assume that there are statistically significant differences between the results of the tribal and dimensional tests of the experimental and controlled research groups in the performance of the skills of preparing and overwhelming volleyball, and there are statistically significant differences between the results of the dimensional tests of the experimental research groups and the control according to the cognitive preference in the knowledge outcome and learn my skill Receiving the transmission and sending volleyball, I adopted the experimental research curriculum by designing the experimental groups and the two equal controls, while the research community is determined by the students of the second stage in the Faculty of Physical Education, Sports Science/University of Baghdad, for the academic year (2023/2024), the total number of (361) students distributed over (9) study people, The research sample was chosen from them randomly, two divisions, two to reach (64) students by (17.279%) of this society, and then one of these two divisions was chosen randomly, so that its students were the experimental group from the Division (D) and the other from the Division (C) officer with a number of (32) students Each group of them, as was chosen by the students of the Division (G) (10) students of the sample of exploratory experience representing (2.77 %) of their origin society, and after identifying the skill technical performance tests for each of the skills, the exercises were prepared and the vocabulary of the Edja model was employed, and applied by the reality An educational unit per week and each skill (4) units to continue the application (8) consecutive weeks and after the end of the experiment, the data was processed with SPSS To be the conclusions and recommendations that the application of the vocabulary of the Edga model in the practical physical education lessons for volleyball has proven suitable for students of the second stage in the College of Physical Education and Sports Sciences, and the Edga model application helps improve the performance of the skills of preparing and overwhelming volleyball in volleyball for students of the second stage in the Faculty of Physical Education and Sciences Sports, they outperform their performance in students who are studying in the way used in the practical lesson, and it is necessary Attention to the inclusion of the vocabulary of the Edga model and its inclusion in educational exercises, so that the teaching of the mind and the body is walking side by side in achieving the goals of the physical education studied practical.